Terrorism post 11 September 2001: the economic globalisation and religion (Islamophobia) perspective - Mustafa, Mahfudzah; Ahmad, Zaid; Jawan, Jayum; Md Nor, Mohd Sabri; Othman, Muhammad Helmi (Human Resource Management Academic Research Society, 2021)
The end of Cold War has seen war as not only based on the question of ideology such as the clashes between socialism and capitalism, communism versus liberal democracy but it has radically changed into discourses and questions of identity, civilisations and religion. "War against Terrorism" sponsored by the United States of America has changed the paradigm of a majority of scholars in repositioning the concept of terrorism and the factors that lead to terrorism such as global Islamophobia. The existence of non-state actors such as Al Qaeda, DAESH or IS serves as indicators that non-state actors can challenge the state actors. Economic globalization also undeniably contributes as a factor to terrorism due to feelings of dissatisfaction towards the inequality and the gap among the nation-states. This study seeks to analyze the concept of terrorism after the 11 September 2001 event. This study further elaborates how the issues of globalization and religion became the pivot for terrorism activities. This study uses the qualitative method. The technique used is more towards analyzing comparatively or a discourse analysis on case studies relevant to the research. Primary and secondary data are also used.